HPLC profiling of phenolics and flavonoids of Adonidia merrillii fruits and their antioxidant and cytotoxic properties - Vafaei, Ali; Mohamad, Jamaludin; Karimi, Ehsan (Taylor & Francis, 2019)
In this study the antioxidant and cytotoxicity activity of the Adonidia merrillii fruits were investigated using different solvent polarities (methanol, ethyl acetate and water). The results showed that the total phenolic and flavonoid contents of the methanolic extract was higher compare with other extract with respective values of 17.80 ± 0.45 mg gallic acid equivalents/g dry weight (DW) and 5.43 ± 0.33 mg rutin equivalents/g DW. Beside that The RP-HPLC analyses indicated the presence of gallic acid, pyrogallol, caffeic acid, vanillic acid, syringic acid, naringin and rutin. In the DPPH, NO2 and ABTS scavenging assays, the methanolic extract exhibited higher antioxidant activity as compared to the ethyl acetate and water extracts. The extracts exhibited moderate to weak cytotoxic activity in the assays using human hepatocytes (Chang liver cells) and NIH/3T3 (fibroblasts cell) cell lines. The findings showed the Adonidia merrillii fruit extracts to possess considerable antioxidant and cytotoxicity properties. The fruit, therefore, is a potential candidate for further work to discover antioxidant and cytotoxic drugs from natural sources. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.